Optimal redesign of the pressurized network of section 01 of 001 irrigation district Pabellon de Arteaga, Aguascalientes - Galván-Cano, Osvaldo; Exebio-García, Adolfo Antenor (REVISTA TERRA LATINOAMERICANA, 2020)
Water as resource is increasingly more restricted, agriculture is the sector with the highest water demand, thus, irrigation infrastructure that is able to optimize and supply water to the crops is needed. The purpose of our study was to redesign and optimize section 01 of the 001 (DR 001) irrigation district, Pabellon de Arteaga, Aguascalientes, for the network to fulfill the water requirements of crops with demand-based irrigation supply. The first Clément formula was applied for the hydraulic capacity of the network sections and linear programming to determine the optimal diameters of the pressurized network, minimizing the cost of the pipeline, which is one of the components with the highest budget in an irrigation system. The minimum and maximum speed, length of each section, minimum pressure at the nodes and a minimum flow rate of 20 L s‑1 were employed as restrictions. The results suggest important modifications with respect to the installation, currently, the sections of the network belong to class 5, and the redesign mostly assigned class 7. In addition, 10, 61% of the sections increased their diameter, with a minimum total cost of $ 6 968 266 in terms of polyvinyl chloride (PVC) pipe. Moreover, the restriction of the 4 pressure regulating valves (PRV) within section 01 was also removed for it to operate with the whole pressure of the entrance of the section.